INSTITUTIONAL MECHANISMS OF IMPLEMENTATION AND CONTROL OF THE STATE POLICY OF STRENGTHENING THE ECONOMIC SECURITY OF UKRAINE - GARAFONOVA, OLGA; KRAVCHYK, YURII; YANKOVYI, ROMAN; YASHCHENKO, INNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article emphasizes the urgency of forming and implementing in Ukraine a state policy to strengthen the economic security of the state, in particular in view of the strengthening of external and internal hybrid risks and threats. The composition and essential-methodical provisions of such mechanisms of strengthening the economic security of Ukraine as normative-legal, organizational-administrative, financial-resource, information-methodical, monitoring, control and adjustment are determined. Emphasis is placed on the high level of need to improve the current methodological recommendations for assessing the economic security of the state of the Ministry of Economy of Ukraine from 2013. The key areas for improving methodological recommendations are indicated - breeding of innovation and investment components, inclusion of additional indicators that will more systematically characterize the development of entrepreneurship and competition in the domestic market of Ukraine, the formation and implementation of innovation and technological potential of the national economy. The applied significance of the research results is to determine the vectors of improvement of the national state policy of deterrence of hybrid aggression, which is currently characterized by insufficient structural connection with European and world standards in economic, information and social security and due to lack of common political will and vision of state social vector. confrontation of hybrid threats both by central legislative and executive bodies, and by local self-government bodies. The scientific novelty of the research results is to identify areas for improvement of regulatory and methodological recommendations for assessing the level of economic security of the state, in particular on the dilution of innovation and investment components, the inclusion of additional indicators that will more systematically characterize the development of entrepreneurship and competition in Ukraine.